Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.